Conservative treatment of a radicular cyst in a 5-year-old child: A case report - Delbem, Alberto Carlos Botazzo [UNESP]; Cunha, Robson Frederico [UNESP]; Vieira, A. E M [UNESP]; Pugliesi, D. M C [UNESP] (Wiley, 2003)
The present report describes the management of a radicular cyst in a 5-year-old child. The treatment comprised extraction of the primary teeth involved followed by marsupialization. A removable appliance with a resin extension penetrating into the cystic cavity was used to help decompress the lesion. This treatment allowed rapid healing of the lesion and eruption of the permanent incisors without the need for orthodontic treatment.
Keywords: analgesic agent; anamnesis; case report; clinical examination; clinical feature; cytopathology; dental surgery; dentistry; differential diagnosis; follow up; histopathology; hospital discharge; human; incisor; jaw radiography; male; odontogenic cyst; patient referral; pediatric hospital; physical examination; preschool child; surgical technique; tooth crown; tooth eruption; Child, Preschool; Decompression, Surgical; Humans; Male; Maxillary Diseases; Radicular Cyst; Tooth Extraction